Antiquitized emblems of Andrea Alciato - E.S. Danilov (Ученые записки Казанского университета: Серия Гуманитарные науки)
Emblems are visible metaphors, a synthesis of words and images. They traditionally embodied simple earthly truths, moral standards, and political principles. Emblem studies is a special historical discipline studying symbolic representations of certain notions or ideas. Scholars distinguish several sources of this discipline: Egyptian hieroglyphics; epigrammatic, fabular, and numismatic heritage of the Classical Antiquity; medieval fabliau and proverbs; bestiary images of both epochs. In this paper, the “Emblemata” created by Andrea Alciato (1492–1550), a Late Renaissance writer and erudite, was analyzed. Particular attention was drawn to certain groups of mythological characters and historical personalities of the classical antiquity. The prevailing appeal to mythological creatures was noticed. The main works of Greek and Roman authors, which became sources for A. Alciato, were revealed. In particular, the “Palatine Anthology”, the fables of Aesop and Avian were an important source of inspiration for A. Alciato. The analysis is based on 155 symbolic compositions (73% of the total number) and indicates a close connection of A. Alciato’s emblematic intention with the literary heritage of the classical antiquity. The book of the Italian humanist was originally intended for the erudite public. The theoretical ideas of subsequent emblematists were also based on Greco-Roman sources. A. Alciato was the first in this genre.